The flowering thorn : international ballad studies - McKean, Thomas A., 1961- (Utah State University Press, 2003)
The flowering thorn expresses the dual nature of the ballad: at once a distinctive expression of European tradition, but also somewhat tricky to approach from a scholarly perspective, requiring a range of disciplines to illuminate its rich composition.